Activation and Functional Priming of Blood Neutrophils in Non-Alcoholic Fatty Liver Disease Increases in Non-Alcoholic Steatohepatitis - Lauszus JS (Dove Medical Press, 2021)
Johanne Sloth Lauszus,1 Peter Lykke Eriksen,1 Mette Mejlby Hansen,1 Lotte Lindgreen Eriksen,1 Debbie Lindsay Shawcross,2,3 Hendrik Vilstrup,1 Karen Louise Thomsen,1 Sidsel Stoy1 1Department of Hepatology and Gastroenterology, Aarhus University Hospital, Aarhus, Denmark; 2Institute of Liver Studies, School of Immunology and Microbial Sciences, Faculty of Life Sciences and Medicine, King’s College London, London, UK; 3Institute of Liver Studies, King’s College Hospital NHS Foundation Trust, London, UKCorrespondence: Sidsel StoyDepartment of Hepatology and Gastroenterology, Aarhus University Hospital, Palle Juul Jensens Boulevard 99, Aarhus, DenmarkEmail Sidsel_stoy@clin.au.dkIntroduction: In non-alcoholic fatty liver disease (NAFLD), neutrophils in liver infiltrates are activated, which may contribute to disease progression towards non-alcoholic steatohepatitis (NASH). However, the functional status of the blood neutrophils remains unknown and their role in the disease mechanisms is thus uncertain. We therefore characterized activation and function of blood neutrophils in patients with NAFLD in relation to clinical disease markers and the NAFLD plasma milieu.Methods: We studied 20 patients with NAFLD, among these 6 patients with NASH, and 14 healthy persons. Neutrophil activation, interleukin (IL)-8 production and oxidative burst were measured by flow cytometry on participants´ neutrophils and on healthy neutrophils exposed in vitro to plasma from the study participants.Results: Blood neutrophils from the NASH patients showed a doubling in their expression of the activation marker CD62L. Also, all NAFLD patients had 50– 100% increased expression of CD11b. Functionally, NASH neutrophils had 30% elevated IL-8 production and more than doubled spontaneous oxidative burst. In all NAFLD patients, higher spontaneous oxidative burst was associated with worse liver function. Incubation of healthy neutrophils with NAFLD plasma paradoxically slightly reduced CD62L and CD11b expression, and NASH plasma also reduced the frequency of IL-8-producing neutrophils.Conclusion: In NAFLD, blood neutrophils are activated, and in NASH also functionally primed. This suggests a progressive neutrophil aggressiveness already present with liver fat infiltration. However, NAFLD plasma in vitro, if anything, had the opposite effect on the healthy neutrophils so the NAFLD-related neutrophil activation cannot be attributed to humoral factors and remains unexplained.Keywords: neutrophil, non-alcoholic fatty liver disease, non-alcoholic steatohepatitis, oxidative burst, CD11b